Personality, Job Satisfaction and Health - The Mediating Influence of Affectivity - Justina A. V. Fischer; Alfonso Sousa-Poza (Swiss Journal of Economics and Statistics, 2008)
This paper evaluates the relationship between job satisfaction and subjective and objective measures of health of workers over 50 using the Swiss Household Panel (SHP) and cross-sectional data from the Survey on Health, Ageing and Retirement in Europe (SHARE). Methodologically, we address problems of (a) crosssectional causality and (b) absence of objective measures of physical health and intellectual ability. We find a positive link between job satisfaction and various self-report health measures and intellectual ability, but not for physical health. Further analysis with the SHP indicates that job satisfaction serves as transmission channel of working conditions, prior health state and affective mental state for most self-report measures, while for specific health problems such as depressive states and problems with the back a direct beneficial effect of job satisfaction remains.
Keywords: I18; I19; J28; 330; job satisfaction; health; SHARE; affectivity; work conditions